Movement patterns of three species of sparrows in the central Monte desert, Argentina: differences between and within species - Sagario, Maria Cecilia (2014)
Accurate knowledge of the movements of passerine populations in the southern hemisphere is difficult to attain, in part owing to differences in movements between and within species and between and within populations. In temperate South America, descriptions of patterns of movements are often based on reports of local changes in abundance and occurrence of species and there have been few detailed studies of movements at the local population level. We banded and monitored individuals of three species of sparrow – the Many-coloured Chaco-Finch (Saltatricula multicolor), Ringed Warbling-Finch (Poospiza torquata) and Rufous-collared Sparrow (Zonotrichia capensis) in a temperate site in the central Monte desert, Argentina, to evaluate differences in site-attachment between and within species. We found resident populations of all three species, the juveniles of which showed little site-attachment. We also observed a large influx of mobile Ringed Warbling-Finches and Rufous-collared Sparrows during the non-breeding season. We confirmed population partial migration of two subspecies of Rufous-collared Sparrows (and, possibly, a third otherwise resident subspecies), and possibly also within Ringed Warbling-Finches. The influxes of mobile individuals during the non-breeding season may be in response to unpredictable climate and consequent availability of resources, as has been found in arid regions of Australia and Africa. Our results provide a basis for a better understanding of the evolution of movement patterns of birds in temperate South America.